Redox control of magnetic transport properties of a single anthraquinone molecule with different contacted geometries. (March 2017) - Fan, Zhi-Qiang; Sun, Wei-Yu; Jiang, Xiang-Wei; Zhang, Zhen-Hua; Deng, Xiao-Qing; Tang, Gui-Ping; Xie, Hai-Qing; Long, Meng-Qiu
Abstract: Controlling magnetic transport through a single molecule remains one of the most fundamental challenges of spin electronics. Here, we investigate the effects of the redox reaction on the magnetic transport properties of a single anthraquinone (AQ) molecule connected to zigzag graphene nanoribbon electrodes by using the non-equilibrium Green's function formalism with density functional theory. Two kinds of contacted types, isomeric AQ-14 and AQ-15, are considered in this work. The results show the excellent spin-filtering with 100% spin filtering efficiency can be found in AQ-14 molecular device. Redox reaction on the molecule doesn't affect its spin filtering behavior. After the contacted type changing, the spin-filtering behavior is only found in AQ-15 molecular device at the reduced state. When the molecule is oxidized, the α-spin current of the device is reduced dramatically leading to the absence of the spin-filtering behavior. More importantly, the on-off of the α-spin electronic conductance of AQ-15 induced by redox reaction can allow it be designed as a spin current switching. Graphical abstract: